(untitled) (International relations and international law Journal, 2018)
Now terrorism became the real threat not only for the certain states, but also for all world community. Great Britain belongs to those countries in which rather successfully fight against extremism and have certain practices according to prevention of extremist manifestations. In article the conclusion is drawn that the principles of the organization of fight by extremism, and first of all her preventive character and broad cooperation with the population are the reason of successful «prevention of youth extremism in Great Britain». At acquaintance with the documents concerning activities of police of the United Kingdom for prevention and suppression of extremist activity and when viewing a number of the websites belonging to offices of police of Great Britain, the fight against youth extremism having generally preventive character is often conducted not so much globally how many «pointswise» and «precisely». However when developing practical recommendations in the sphere of communication counteraction to terrorism in is necessary to consider both positive, and negative experience, therefore studying of various directions of anti-terrorist activity of the countries of the West is represented relevant and important. Key words: Great Britain, terrorism, extremism, struggle, IRA, MI5, international, national and religious minorities, police.